2014
DOI: 10.1007/s13105-014-0367-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of lycopene-enriched tomato paste on N-nitrosodiethylamine-induced oxidative stress in rats

Abstract: Lycopene is a carotenoid pigment produced by vegetables and fruits, with tomatoes and their processed products being the most abundant sources. A high number of conjugated dienes make lycopene a powerful radical scavenger. Its antioxidant properties are considered to be primarily involved in many beneficial health effects. The present study was designed to assess the protective effect of lycopene-enriched tomato paste against N-nitrosodiethylamine (NDEA)-induced oxidative stress in rats. Forty-eight male Wista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…1.88-fold, which is consistent with earlier reports [13] [27]. Compared with the NDEA group, the hepatic tissue TBARS were significantly reduced in the C3G-150, MAEs-75 and MAEs-150 groups by 39.01%, 40.85%, and 44.52%, respectively ( Table 6, P < 0.001).…”
Section: Antioxidative Effect Of Maes On Tbars and Related Antioxidansupporting
confidence: 91%
See 2 more Smart Citations
“…1.88-fold, which is consistent with earlier reports [13] [27]. Compared with the NDEA group, the hepatic tissue TBARS were significantly reduced in the C3G-150, MAEs-75 and MAEs-150 groups by 39.01%, 40.85%, and 44.52%, respectively ( Table 6, P < 0.001).…”
Section: Antioxidative Effect Of Maes On Tbars and Related Antioxidansupporting
confidence: 91%
“…Our results showed that NDEA administration changes the antioxidant status, leading to oxidative stress, Whereas MAEs can inhibit lipid peroxidation and enhance antioxidant capacity, so the prevention effect of MAEs against NDEA-induced hepatocarcinogenesis in rats may be closely related to its antioxidant activity. Chen et al [13] [18] [27] also found that anthocyanins and water extracts from mulberry fruit can scavenge free radicals and shown concentration-dependent antioxidant activity in vitro.…”
Section: Antioxidative Effect Of Maes On Tbars and Related Antioxidanmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of the polyene provided protection from mitochondrial dysfunction and OS (Snadhir, Mehrotra, & Kamboj, 2010). The compound is a powerful radical scavenger and its AO properties are involved in many health effects (Kujawska, Ewertowska, Adamska et al, 2014). A tomato paste suppressed OS in rats.…”
Section: Polyene-lycopenementioning
confidence: 99%
“…Some studies into lycopene determined that it decreases levels of malondialdehyde (MDA), a product known to correlate with oxidative damage thanks to its association with the oxidation of fatty acid, and that lycopene increases the activities of such antioxidants as superoxide dismutases (SOD) and glutathione peroxidase (GP) [14]. A studyclearly demonstrate that lycopene is able to suppress NDEA-induced oxidative stress in rats [19].Altough a lot of studies were focused on the antioxidant and anti- …”
Section: Introductionmentioning
confidence: 99%